Assessing the Moderating Role of Risk Management Capabilities in the Relationship Between Service Innovation and Financial Performance of Insurance Firms - Yankson, Isaac Obeng; Kwaning, Emmanuel Addai; Dogbe, Courage Simon Kofi (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The study assessed the moderating role of risk management capabilities in the relationship between service innovation and financial performance of insurance firms. A survey research design was adopted, with a quantitative research approach. The population of comprises life and non-life insurance companies in Ghana, numbering 39. There were 17 insurance firms selected for the study, from which 161 management staff were drawn as respondents. Data was analyzed using Structural Equation Modelling (SEM). The study concludes that, risk management capability had a positive moderative effect on the relationship between service innovation and financial performance of insurance companies in Ghana. This notwithstanding, both service innovation and risk management capability had a direct significant positive effect on financial performance of insurance firms. For stronger financial position, firms should endeavor to invest in both service innovation and effective risk management practices. The main contribution of this study centers on the interactive effect of service innovation and risk management capability. Although direct effects of service innovation and risk management, on financial performance have been established in literature, the interactive effect of these two predicting variables has not been well established in literature.